Evidence and Characteristics of Traditional Chinese Medicine for Coronary Heart Disease Patients With Anxiety or Depression: A Meta-Analysis and Systematic Review - Wang, Baofu; Teng, Yu; Li, Yang; Lai, Sijia; Wu, Yang; Chen, Shiqi; Li, Tong; Han, Xiaowan; Zhou, Hufang; Wang, Yu; Lu, Ziwen; Li, Haiyan; et al. (Frontiers in Pharmacology, 2022)
Aims: The objective of this study was to assess the efficacy and potential mechanisms of Chinese herbal medicine (CHM) for treating coronary heart disease (CHD) patients with anxiety or depression. Methods: A systematic literature search was performed. Screening studies, extracting data, and assessing article quality were carried out independently by two researchers. The active ingredients of CHM for the treatment of CHD with anxiety or depression were analyzed by the network pharmacology, and the main potential mechanisms were summarized by the database of Web of Science. Results: A total of 32 studies were included. The results showed that compared with the blank control groups, CHM was more beneficial in treating anxiety or depression in patients with CHD [anxiety: OR = 3.22, 95% CI (1.94, 5.35), p < 0.00001, I2 = 0%; depression: OR = 3.27, 95% CI (1.67, 6.40), p = 0.0005, I2 = 0%], and the efficacy of CHM was not inferior to that of Western medicine (WM) [anxiety: OR = 1.58, 95%CI (0.39, 6.35), p = 0.52, I2 = 67%; depression: OR = 1.97, 95%CI (0.73, 5.28), p = 0.18, I2 = 33%,]. Additionally, CHM also showed a significant advantage in improving angina stability (AS) in CHD patients with anxiety or depression compared with blank groups [anxiety: SMD = 0.55, 95%CI (0.32, 0.79), p < 0.00001, I2 = 0%; depression: p = 0.004] and WM groups [anxiety: SMD = 1.14, 95%CI (0.80, 1.47), p < 0.00001, I2 = 0%; depression: SMD = 12.15, 95%CI (6.07, 18.23), p < 0.0001, I2 = 0%]. Angina frequency (AF) and electrocardiogram (ECG) analysis after using CHM demonstrated similar trends. Based on the network pharmacology, quercetin, kaempferol, luteolin, beta-sitosterol, puerarin, stigmasterol, isorhamnetin, baicalein, tanshinone IIa, and nobiletin were most closely and simultaneously related to the pathological targets of CHD, anxiety, and depression. The main underlying mechanisms might involve anti-damage/apoptosis, anti-inflammation, antioxidative stress, and maintaining neurotransmitter homeostasis. Conclusion: CHM exhibited an obvious efficacy in treating CHD patients with anxiety or depression, especially for improving the symptom of angina pectoris. The most active compounds of CHM could simultaneously act on the pathological targets of CHD, anxiety, and depression. Multiple effective components and multiple targets were the advantages of CHM compared with WM.